Influence of Biologically Oriented Preparation Technique on Peri-Implant Tissues; Prospective Randomized Clinical Trial with Three-Year Follow-Up. Part I: Hard Tissues - Agustín Panadero, Rubén; Bustamante Hernández, Naia; Solá Ruíz, María Fernanda; Zubizarreta Macho, Álvaro; Fons Font, Antonio; Fernández Estevan, Lucía (My University, 2021)
Purpose: The objective of this prospective randomized clinical trial (RCT) was to analyze and compare the clinical behavior of three types of prosthesis supported by single implants in the posterior region after three years functional loading. Materials and Methods: Seventy-five implants were divided into three groups according to the type of prosthetic restoration: screw-retained crown (Group GS); cemented crown without finishing line (biologically oriented preparation technique) (Group GBOPT); and conventional cemented crown with finishing line (Group GCC). The clinical behavior of each restoration type was analyzed after 3 years functional loading by analyzing radiographic peri-implant bone loss. Results: GBOPT obtained the least bone loss (p < 0.01) in comparison with GS and GCC. Conclusions: Bone loss around implants is related to the type of prosthetic restoration it supports, whereby cemented BOPT crowns present less bone loss.